Biochemical responses in Danio rerio following exposure to CdS and ZnS Quantum Dots. (29th March 2019) - Rocha, Alexandre; Sousa, David; Ferreira, Isabel; Diniz, Mário Sousa
Abstract : Introduction: As the interest and progress in the field of nanotechnologies expands, new nanomaterials are being launched as an integral part of commercial products or innovative methods in several scientific areas. Quantum Dots (QDs) are a type of nanomaterials that are released to aquatic ecosystems through industrial waste, being a potential risk to the water quality. This study aims to evaluate the stress responses in Danio rerio following exposure to different concentrations of two types of QDs (CdS and ZnS). Materials and methods: The fish (n = 40) were randomly distributed by eight glass containers (1000 mL volume). Two glass containers contained dechlorinated filtered tap water (controls). The fish were exposed to different concentrations of QDs: CdS and ZnS (10 µg.L −1, 100 µg.L −1 and 1000 µg.L −1 ) for 7 days. At the end of the exposure period, fish were collected and homogenized in a phosphate saline solution buffer (PBS, pH = 7.4), centrifuged (10, 000 xg for 15 min at 4ºC) transferred to microtubes and frozen (-80ºC) until analysis. Oxidative stress enzymes activities (glutathione-S-transferase, superoxide dismutase and catalase), Ubiquitin and lipid peroxidation were determined as previously described [1–3 ]. For the results analysis, since assumptions (normal distribution and homoscedasticity) were not met, it was used the non-parametric Mann-Whitney U test. Results and discussion: In general, after 7 days the fish exposed to CdS Quantum Dots did not show a significant increase of the GST, SOD (% inhibition) and Lipid peroxidation for the tested concentrations when compared to the controls. However, the results following the exposure to ZnS QDs showed significant differences (p < 0.05) in comparison to the controls. Regarding CAT results, significant differences (p < 0.05) were found between fish exposed to 100 µg.L −1 of ZnS QDs and the controls. With respect to the total antioxidant capacity (TAC), the results show slight variations but with no significant differences (p > 0.05) between tested concentrations. Concerning total ubiquitin, a significant increase (p < 0.05) was detected between fish exposed to 10 µg.L −1 of CdS QDs in comparison to controls, while a significant decrease was determined between fish exposed to 1000 µg.L −1 of ZnS QDs and the controls. Conclusions: The study suggests that the ZnS QDs are probably more capable to cause sublethal effects in zebrafish after 7 days of exposure than CdS. We can speculate that this can be due, in some extent, to different degrees of QDs aggregation and possibly higher rates of dissociation of Zn ions from the QDs which in turn cause the observed toxicity in fish exposed to Zn QDs. Nonetheless, more studies are needed to clarify this issue such as tissue content of each QDs tested and perform studies on metal dissociation from QDs.